Pengaruh Pelayanan, Religiusitas Dan Bagi Hasil Terhadap Minat Nasabah Dalam Menabung Di Bank Syariah Indonesia Banyuwangi - Ustanti, Mira; Reva Dwi Melania; Moh. Qowim (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2023)
Abstract The purpose of this study is to determine the effect of service (X1), religiosity (X2) and profit sharing (X3) partially or simultaneously on interest in saving (Y) at Bank Syariah Indonesia Banyuwangi. This research was obtained from using quantitative research using primary data obtained from the results of the distribution of questionnaires or questionnaires. The sampling technique in this study used Probity Sampling with the type of Simple Random Sampling. Respondents used in this study were 40 people who saved at Bank Syariah Indonesia. The results of this study indicate that the t test test shows that the service has a significant effect on saving interest at BSI Banyuwangi, having a tcount of 4,573 which is greater than ttable of 0.132 with a significant probability level of 0.02 which is smaller than 0.05. Religiosity has a significant effect on saving interest at BSI Banyuwangi. It has a t count of 4.339 which is greater than t table of 0.132 with a significant level of 0.03 which is smaller than 0.05. Profit sharing has a significant effect on interest in saving at BSI Banyuwangi has a t count of 2.304 which is greater than t table 0.132 with a significant level of 0.02 which is smaller than 0.05. And through the F test, it is known that service (X1), Religiosity (X2), and Profit Sharing (X2) have a simultaneous effect on interest in saving at BSI Banyuwangi. The Adjusted R square figure of 0.929 indicates that 92.9% of the variation in saving interest can be explained by the three independent variables used in the regression equation. While the remaining 7.1% is influenced by other variables outside the three used in this study.